Comparative chloroplast genomics provides insights into the genealogical relationships of endangered Tetraena mongolica and the chloroplast genome evolution of related Zygophyllaceae species - Yang, Yanci; Jia, Yun; Zhao, Yanling; Wang, Yonglong; Zhou, Tao (Frontiers in Genetics, 2022)
A comprehensive understanding of genetic background for rare species will provide an important theoretical basis for the future species management, monitoring and conservation. Tetraena mongolica is restrictedly distributed in the western Ordos plateau of China and has been listed as a national protected plant. We generated 13 chloroplast (cp) genomes of T. mongolica (size range of 106,062–106,230 bp) and conducted a series of comparative analyses of six Zygophyllaceae cp genomes. T. mongolica cp genome exhibited a quadripartite structure with drastically reduced inverted repeats (IRs, 4,315 bp) and undergone the loss of a suit of ndh genes and a copy of rRNAs. Furthermore, all the T. mongolica populations were divided into two genetic groups based on complete cp phylogenomics. In addition, notably variable genome size, gene order and structural changes had been observed among the six Zygophyllaceae cp genomes. Overall, our findings provide insights into the cp genome evolution mode and intraspecific relationships of T. mongolica, and provide a molecular basis for scientific conservation of this endangered plant.